Water Quality in Selected Water Springs in Banda, Kampala-Uganda (Student's Journal of Health Research Africa, 2022)
Background   Groundwater is the main source of water for drinking and other domestic use for the people of Banda. The main objective was to assess water quality in selected springs in Banda in the Kampala district. The specific objectives were to determine the pH, electroconductivity, alkalinity, turbidity, total dissolved solids, mineral, and heavy metal content of the water samples as well as their fecal coliform counts. MethodologyTwo samples were collected from each spring at an interval of one week. Electroconductivity and pH measurements were done on-site using a conductivity meter and a digital pH meter respectively. Alkalinity and chlorine content was determined by titration, total dissolved solids by the gravimetric method, and turbidity by use of a turbidity meter while Atomic Absorption Spectroscopy was used for both mineral and heavy metal analysis. Fecal coliforms were enumerated using the membrane filtration method. Minerals assessed were calcium, potassium, sodium, chlorine, and magnesium while lead, cadmium, copper, and arsenic were the heavy metals of interest.ResultsResults showed the following concentration ranges: pH (4.71-6.26), electro conductivity (218.80-621.00 µS/cm), alkalinity (10.35-60.40 mg/L), total dissolved solids (111.90-323.20 mg/L), turbidity (2-3 FTU), Sodium (16.11-34.45mg/L), Chlorine (17.73-49.25 mg/L), Calcium (4.81-20.05 mg/L), Magnesium (2.50-4.87 mg/L), Potassium (4.05-11.85 mg/L) and Lead (0.17-0.24 mg/L), Copper (1.69-2.66 mg/L), Cadmium (0.02-0.08 mg/L), Arsenic (0.005-0.01 mg/L). Fecal coliforms ranged between 1150 and 2700 colony-forming units/100ml.ConclusionFrom analyses carried out, spring water from Banda is chemically and microbiologically unsuitable for drinking-water purposes except after some form of treatment.RecommendationsNational Water and Sewerage Cooperation should take urgent action by carrying out more research on all water springs in this area.Residents of this area should be encouraged to use tap water than spring water until further analyses are carried out.
Keywords: Banda,; groundwater; quality; drinking water; minerals; heavy metals,; fecal coliforms